Transformational giftedness: rethinking our paradigm for gifted education - Sternberg, Robert J. (Roeper review, 2020)
In this article, I discuss two kinds of giftedness, transactional and transformational. Transformational giftedness is giftedness that is transformative. Transformationally gifted individuals seek positively to change the world at some level—in their own way, to make the world a better place. Transactional giftedness is giftedness that is based on exchange. It is tit-for-tat in nature. The individual is identified as gifted and then expects and is expected to do something in return. That something, for children, is typically high-level performance in academic coursework. Society also may expect that the individual later in life will continue to show high educational achievement. The two kinds of giftedness are not inborn. Rather, they are shaped through life in school and in the home interacting with the personal attitudes toward life of the gifted individual.
Gesehen am 06.06.2025